REDEFINING ONLINE LEARNING WITH GREAT SAGE: A SCALABLE, ROLE-BASED EDUCATION SYSTEM - Pandey, Ayush; Srivastava , Aditya; Jaiswal, Rohit; Srivastava, Balkrishna; Singh, Er. Anurag (International Journal of Research -GRANTHAALAYAH, 2025)
This Paper presents Great Sage, a powerful Learning Management System (LMS) designed to address the limitations of existing platforms by offering features personalized learning, intelligent content creation, and infrastructure that can be scaled based on the requirement. After a thorough comparative analysis of existing LMS solutions, the study highlights gaps in customization, monetization, and learner engagement. This research also outlines the technical architecture and future potential of platform, making it a comprehensive solution for next-gen digital learning.